METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS AND ITS ANTIBIOTIC SENSITIVITY PATTERN IN PATIENTS WITH VESICULOBULLOUS DISORDERS - Hamid Ur Raziq; Ullah, Ghafoor; Ali, Farhad; Ziaulhaq , Muhammad; Ali, Rahmat (Journal of Ayub Medical College Abbottabad, 2023)
Background: Vesiculobullous disorders are among the leading causes of admission to dermatology. These are characterized by distinct mucocutaneous involvement and by the development of vesicles and bullae (i.e. blisters). Methicillin-resistant Staphylococcus aureus (MRSA) is a group of gram-positive bacteria distinct from other strains of Staph aureus. As the susceptibility of bacteria to antibiotics varies from region to region and from time to time, this study will determine the pattern of antimicrobial susceptibility of MRSA isolates to the commonly prescribed antibiotics in our population. The objective is to determine the frequency of methicillin-resistant Staphylococcus aureus and its antibiotic sensitivity pattern in patients with vesiculobullous disorders admitted to the Dermatology unit of Lady Reading Hospital (LRH), Peshawar. It was Cross-sectional and carried out in study Department of Dermatology, Lady Reading Hospital, Peshawar from Oct 23, 2020, to Apr 22, 2021. Methods: This study was carried out over 132 patients. After consent, Swabs of pus from the Vesiculobullous disorders were taken from all the patients and sent to a laboratory for culture. Staphylococcus aureus (MRSA) was labelled as Staphylococcus aureus bacteria by Kirby-Bauer disc diffusion method using oxacillin (1 Î¼ gm.) disc on Mueller-Hinton agar (HiMedia Labs, Mumbai) with 24 hours incubation at 35°C. Results: In this study, 132 patients were observed. The average age was 44.44 years ±13.74 SD. Male to female ratio was 1.30:1. There were 44(33.33%) patients who showed Methicillin Resistant Staphylococcus aureus (MRSA) in vesiculobullous disorders patients. Conclusion: In our population, the frequency of staphylococcus aureus bacteria in vesiculobullous disorders is high so it will be considered while treating such patients.